“Estudio del proceso de producción de lácteos, en el laboratorio de la Unidad Académica CAREN-UTC en el 2016, elaboración de una Manual de Buenas Prácticas de Manufactura”. - Rojas Guambiango, Edison Fabian (2016)
This research project focused on the study of the dairy production process, emphasizing food handling and hygiene in the laboratory of the Technical University of Cotopaxi, applying a field investigation, information was obtained from different components such as: facilities, equipment, utensils, personnel obligations, raw materials, production operations, packaging, storage, distribution, and quality assurance, which are important for the safety of products such as pasteurized milk, cheese, yogurt, and ice cream.